(untitled) (Research, Society and Development, 2024)
The creation of the National Immunization Program (PNI) had an impact on the morbidity and mortality of the Brazilian population, enabled advances in public health in Brazil and validated immunization as one of the most important interventions of public health services. However, in recent years, there has been a decrease in immunization rates for some diseases, mainly due to the COVID-19 pandemic, the overload of the health system and the drop in face-to-face attendance at health services, as well as the dissemination of fake news about the effectiveness of vaccines. Therefore, the objective of this study is to evaluate the possible influence and possible damage of the COVID-19 pandemic on childhood vaccination coverage from January 2018 to October 2022. This is a cross-sectional quantitative analytical study, carried out through consultation of the database of the Department of Informatics of the Unified Health System (DATASUS). To this study were selected global percentage data on vaccination coverage of the child population, aged 0 to 10 years, between the aforementioned years, in the North, Northeast, South, Southeast and Midwest regions. Through the analysis of the collected data, it can be observed that there was a significant change in the absolute values of the vaccine coverage of the Tetra Viral and Febre Amarela vaccines, thus, noticing the influence of COVID-19 in the vaccine reach. It is expected that the data presented in this research will contribute to the elaboration of more effective public policies to promote the health and well-being of the population.